Diseño de un sistema de comercialización y abastecimiento de productos de primera necesidad a través de centros comunitarios en la comuna Leopoldo Nicolás Chávez ubicada en la parroquia de Tumbaco, Distrito Metropolitano de Quito. - Campoverde Rivera, Carla Fernanda (2015)
This degree work provides a marketing and supply system design about first need products through community centers in the commune Leopoldo Nicholas Chavez located in the Parish of Tumbaco, Metropolitan District of Quito. In the first chapter, the theoretical basis for understanding and facilitating the proposal are developed. Thus, topics such as: production, agricultural production, stage of production, marketing, marketing system, marketing center, supply center, community centers and solidary economy are carried out. In the second chapter, the characterization, study and current situation of the commune are made as well as the research design to be applied, ending with the presentation and result analysis. In the third chapter, elements for project implementation were established and developed. These ones are: the macro location and micro location of the company, requirement of equipment and furniture, company incorporation, organizational structure, marketing mixture, mision and vision about the center, procurement process, marketing process, investment, projected costs and expenses, projected sales and profitability analysis.